2019
DOI: 10.1021/acs.jpcc.8b10768
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Evidence of Solvent-Mediated Excited-State Dynamics in a Functionalized Iron Sensitizer

Abstract: The solvent-mediated excited-state dynamics of the COOH-functionalized Fe-carbene photosensitizer [Fe(bmicp) 2 ] 2+ (bmicp = 2,6-bis(3-methyl-imidazole-1-ylidine)-4-carboxypyridine) is studied by time-dependent density functional theory (TD-DFT), as well as classical and quantum dynamics simulations. We demonstrate the crucial role of the polar acetonitrile solvent in stabilizing the MLCT states of the investigated molecule using the conductor polarizable continuum (CPCM) model. This leads to dynamics that avo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
55
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 33 publications
(56 citation statements)
references
References 74 publications
1
55
0
Order By: Relevance
“…Interestingly, this electron injection yield exceeds the 3 MLCT yield we observe for [Fe(bmip)2] 2+ dissolved in acetonitrile. Given the expected sensitivity of the branching ratio to small changes in the potential energy landscape, the higher yield for charge injection could result from the red shifted MLCT energies of the COOH-functionalized Fe carbene photosensitizer, differences in the solvation response [57], and the potential for electron injection of electrons from 3 MC excited states. In summary, the observed population dynamics highlight the critical role of 3 MC excited states in the MLCT relaxation of [Fe(bmip)2] 2+ .…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, this electron injection yield exceeds the 3 MLCT yield we observe for [Fe(bmip)2] 2+ dissolved in acetonitrile. Given the expected sensitivity of the branching ratio to small changes in the potential energy landscape, the higher yield for charge injection could result from the red shifted MLCT energies of the COOH-functionalized Fe carbene photosensitizer, differences in the solvation response [57], and the potential for electron injection of electrons from 3 MC excited states. In summary, the observed population dynamics highlight the critical role of 3 MC excited states in the MLCT relaxation of [Fe(bmip)2] 2+ .…”
Section: Discussionmentioning
confidence: 99%
“…53 The resolution of identity 54 and chain of spheres 55 (RIJCOSX) methods were utilized to approximate the two electron integrals. We recently have shown that the excited-state PESs of [Fe(bmip) 2 ] 2+ are not influenced by a polar solvent, such as acetonitrile; 56 we thus carried out all TD-DFT calculations in vacuum. As these calculations lead to a set of adiabatic states, a diabatization procedure is needed to transform into a diabatic electronic basis required for QD simulations.…”
Section: B the Hamiltonianmentioning
confidence: 99%
“…In particular, the decomposition of the overall signal into components by electronic states is very valuable, as this is not accessible from elastic XDS experiments. Based on a recent computational study, 56 the solute dynamics of the investigated [Fe(bmip) 2 ] 2+ complex should not be affected by a polar solvent, such as acetonitrile. However, this is clearly not true for other molecules, 56,70,71 which thus require the inclusion of the solvent, even for simulating the solute difference scattering.…”
Section: Concluding Remarks and Outlookmentioning
confidence: 99%
“…This makes the iron carbene complexes interesting as a promising new class of photosensitizers, with recently demonstrated capability to inject electrons efficiently into a TiO 2 substrate, and carry out bimolecular oxidation and reduction processes . Ultrafast optical measurements in combination with quantum‐chemical calculations have provided significant insight into the excited state structure underlying this remarkable improvement of photochemical properties …”
Section: Introductionmentioning
confidence: 99%
“…[15,17] Ultrafast optical measurements in combination with quantum-chemical calculations have provided significant insight into the excited state structure underlying this remarkable improvement of photochemical properties. [23,24] As an element-specific technique,X -ray spectroscopy is apowerful tool to probe the electronic structure of the metal site and surrounding ligands.With the recent advent of X-ray free electron laser (XFEL) facilities with high flux and at emporal resolution better than 30 fs, [25] it has become possible to identify the nature of the excited states directly. [10,[26][27][28][29][30][31][32] In these studies,t he oxidation state,s pin, and charge-transfer character of the molecular state were identified by modeling the measured time-resolved spectra with al inear combination of measured or calculated static reference spectra.…”
Section: Introductionmentioning
confidence: 99%